Gut Microbiota–Medication Interaction in Rheumatic Diseases - Zhang, Lingshu; Chu, Cong-Qiu (Frontiers in Immunology, 2021)
Besides its contribution to the development of rheumatic diseases, the gut microbiota interact with anti-rheumatic drugs. The intestinal microbiota can directly metabolize many drugs and indirectly change drug metabolism through a complex multi-dimensional interaction with the host, thus affecting individual response to drug therapy and adverse effects. The focus of the current review is to address recent advances and important progress in our understanding of how the gut microbiota interact with anti-rheumatic drugs and provide perspectives on promoting precision treatment, drug discovery, and better therapy for rheumatic diseases.